Hydration, sweat and thermoregulatory responses to professional football training in the heat - Duffield, R.; McCall, A.; Coutts, A. J.; Peiffer, J. J. (Journal of Sports Sciences, 2012)
This study examined the relationship between intensity of training and changes in hydration status, core temperature, sweat rate and composition and fluid balance in professional football players training in the heat. Thirteen professional football players completed three training sessions; "higher-intensity" (140 min; HI140), "lower-intensity" (120 min; LI120) and "game-simulation" (100 min; GS100). Movement demands were measured by Global Positioning System, sweat rate and concentration were determined from dermal patches and body mass change. Despite similar environmental conditions (26.9 ± 0.1°C and 65.0 ± 7.0% relative humidity [Rh]), higher relative speeds (m/ min) and increased perceptions of effort and thermal strain were observed in HI140 and GS100 compared with LI120 (P < 0.05). Significantly (P < 0.05) greater sweat rate (L/h) and electrolyte losses (g) were observed in HI140 and GS100 compared with LI120. Rate of rise in core temperature was correlated with mean speed (r = 0.85), session rating of perceived exertion (sRPE) (r = 0.61), loss of potassium (K+) (r = 0.51) sweat rate (r = 0.49), and total sweat loss (r = 0.53), with mean speed the strongest predictor. Sodium (Na+) (r = 0.39) and K+ (r = 0.50) losses were associated with total distance covered. In hot conditions, individualised rehydration practices should be adopted following football training to account for differences in sweat rate and electrolyte losses in response to intensity and overall activity within a session.